The protective role of SGLT2 inhibitors on aortic aneurysm mediated by oxidative stress and inflammation in type 2 diabetes mellitus - Rujie Zheng; Wenjuan Song; Jie Lu; Mingyue Yuan; Xiaotong Sun; Chengzhi Lu (Cardiovascular Diabetology)
Abstract Background Sodium-glucose transport protein 2 inhibitors (SGLT2i) have been widely used to treat patients with type 2 diabetes mellitus (T2DM) and have demonstrated protective effects against certain cardiovascular diseases. However, no clinical research has been conducted to explore the relationship between SGLT2i and the risk of aortic aneurysm (AA). Methods We extracted and analyzed the data of 4964 patients with T2DM from the First Affiliated Hospital of Zhengzhou University during July 2017 to January 2023. Multivariate Cox models, interaction analysis and Kaplan–Meier curves were performed to approximate the associations of SGLT2i therapy on the risk of AA. A sensitivity analysis was performed to test the robustness of results. Mediation analyses explored the roles of inflammatory (neutrophils, lymphocytes, C-reactive protein and alkaline phosphatase) and oxidative stress (gamma glutamyl transferase, total bilirubin, and uric acid) markers in the associations between SGLT2i and AA. Results A total of 1942 SGLT2 inhibitor (SGLT2i) users (39.12%) and 3022 non-SGLT2 inhibitor (NonSGLT2i) users were included in final analysis. After full adjustment for potential risk factors, SGLT2i patients were associated with a lower risk of aortic aneurysm (HR, 95% CI 0.91, 0.89–0.98, p = 0.001). Dapagliflozin showed the greatest difference for reduction of aortic aneurysm incidence (HR, 95% CI 0.84, 0.80–0.95, p = 0.011). Subgroup analysis indicated that use of SGLT2i lower the risk of aortic aneurysm in some subgroups of T2DM patients. The sensitivity analysis demonstrated the robustness of the results. CRP, lymphocytes, neutrophils, and uric acid were significantly associated with both SGLT2i and AA, with mediation proportions of 13.35%, 8.83%, 9.67% and 31.17%, respectively. Conclusions Our study suggested that patients using SGLT2i may have a lower risk of aortic aneurysm, and this effect could potentially be mediated by inflammation and oxidative stress. Further mechanistic and prospective studies are required to verify this association. Graphical abstract